Business with Chinese counterparts : medical tourism agency for Chinese clientele - Volný, Jan (2016)
The goal of the Masters Thesis is to analyze opportunities and subsequently develop a business plan for a new venture offering medical and health tourism services and tailored solutions to Chinese clientele, which will be formulated based on analysis of Chinese economy, its outbound tourism, business partners, clients cultural specifics and health tourism potential of the Czech Republic. The first chapter aims to analyze the Chinese socio-economic and demographic environment as well as the outbound and medical tourism of China. Next chapter uncovers cultural specifics of Chinese counterparts and customers. The third chapter defines the health and medical tourism and describes the situation in the Czech Republic. After the three theoretical chapters, the practical part in form of business plan for medical tourism agency for Chinese could be prepared.